(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Cystinuria is a rare inherited disorder leading to recurrent nephrolithiasis and potential renal impairment. This report presents the case of a 9-year-old female with elevated urinary cystine, with normal serum biochemical parameters. Ultrasound showed mild hydronephrosis due to bilateral staghorn calculi while intravenous urography demonstrated preserved excretory function. A 99mTc DTPA renogram revealed pelvicalyceal dilatation without obstruction and mild functional impairment of the left kidney, with normal right renal function. The patient underwent left open pyelolithotomy with DJ stent placement. This case highlights the importance of DTPA renogram in detecting early renal dysfunction, differentiating obstruction, and guiding management in pediatric cystinuria to preserve renal function. Bangladesh J. Nuclear Med. 28(2): 399-402, 2025